The Prevalance of Paranasal Sinus Anatomic Variations on Cone Beam Computed Tomography Scan Images of Turkish Population - SADIKOĞLU, AYŞE NUR; NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objectives: The paranasal sinuses include anatomic structures at the maxillofacial region that matters great importance for the surgeons working in the maxillofacial area. The imaging of anatomic variations of the paranasal sinuses is fundamental to evaluate the predisposing factors for the pathologic changes of paranasal sinuses. The aim of this study is to investigate the prevalence of anatomic variations of the paranasal sinueses by retrospective assessment of cone beam computed tomography (CBCT) images. Methods: The paranasal sinus CBCT images of 300 adult patients who were referred to Marmara University, Faculty of Dentistry, Department of Oral Diagnosis and Radiology were evaluated retrospectively. The paranasal sinus variations and their prevalence were recorded. Results: The prevalance of concha bullosa superior was 7,7%, and concha bullosa media was 54,7%. The prevalance of infraorbital ethmoid cell was 15,3%, agger nasi cell was 52,7% and onodi cell was 52.7%. There was no significant differences prevalance of this anatomic variations between males and females or between different age groups. Conclusions: CBCT is a convenient radiographic examination to evaluate the paranasal sinus anatomic variations. Dental surgeons must be aware of suchs anatomic variations of the paranasal sinuses.
Keywords: CBCT; paranasal sinuses; anatomic variations; FRONTAL RECESS; CT; MULTIDETECTOR; REGION; CELLS; PNEUMATIZATION; SURGERY; CBCT